Non-standard English borrowings in German and Russian languages - Lucinski, Kazimir; Zubkov, Eugene (Respectus Philologicus, 2003)
The aim of this work is to show a new method, which gives a possibility to analyze not only loan words but also the borrowing process itself, dependent on the internal system of a language. The subject of the analysis was English borrowings in modern German and Russian non-standard languages. Every non-standard language is an unstable short-term occurrence and depends on speaker's estimation of the words (here we investigated loan-words) he uses. The authors took this fact into consideration along with the changes in the meaning as a word appears on other stylistic levels.
Keywords: loan-words; stylistic level; correlation